Evaluation of a Fully Automatic Deep Learning-Based Method for the Measurement of Psoas Muscle Area - Van Erck, Dennis; Moeskops, Pim; Schoufour, Josje D.; Weijs, Peter J. M.; Scholte Op Reimer, Wilma J. M.; Van Mourik, Martijn S.; Janmaat, Yvonne C.; Planken, R. Nils; Vis, Marije; Baan, Jan; Hemke, Robert; Išgum, Ivana; et al. (Frontiers in Nutrition, 2022)
Background: Manual muscle mass assessment based on Computed Tomography (CT) scans is recognized as a good marker for malnutrition, sarcopenia, and adverse outcomes. However, manual muscle mass analysis is cumbersome and time consuming. An accurate fully automated method is needed. In this study, we evaluate if manual psoas annotation can be substituted by a fully automatic deep learning-based method. Methods: This study included a cohort of 583 patients with severe aortic valve stenosis planned to undergo Transcatheter Aortic Valve Replacement (TAVR). Psoas muscle area was annotated manually on the CT scan at the height of lumbar vertebra 3 (L3). The deep learning-based method mimics this approach by first determining the L3 level and subsequently segmenting the psoas at that level. The fully automatic approach was evaluated as well as segmentation and slice selection, using average bias 95% limits of agreement, Intraclass Correlation Coefficient (ICC) and within-subject Coefficient of Variation (CV). To evaluate performance of the slice selection visual inspection was performed. To evaluate segmentation Dice index was computed between the manual and automatic segmentations (0 = no overlap, 1 = perfect overlap). Results: Included patients had a mean age of 81 ± 6 and 45% was female. The fully automatic method showed a bias and limits of agreement of -0.69 [-6.60 – 5.23] cm2, an ICC of 0.78 [95% CI: 0.74 – 0.82] and a within-subject CV of 11.2% [95% CI: 10.2 – 12.2]. For slice selection, 84% of the selections were on the same vertebra between methods, bias and limits of agreement was 3.4 [-24.5 – 31.4] mm. The Dice index for segmentation was 0.93 ± 0.04, bias and limits of agreement was -0.55 [1.71 – 2.80] cm2. Conclusions: Fully automatic assessment of psoas muscle area demonstrates accurate performance at the L3 level in CT images. It is a reliable tool that offers great opportunities for analysis in large scale studies and in clinical applications.